PENGARUH LINGKUNGAN KERJA INTERNAL TERHADAP KUALITAS PELAYANAN PUBLIK (SUATU STUDI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MINAHASA TENGGARA) - NGONGOLOY, CICILIA; RORONG, ARIE JUNUS; TAMPONGANGOY, DEYSI (Sam Ratulangi University, 2018)
The work environment and the quality of public services are always described as sectors that have an importantrole, because the quality of services provided by employees is an important element for the success of anorganization and one of the requirements for the government in serving every need of society. The result offrequency analysis of internal work environment variable (X) is in moderate category / good enough, that is48,9% while public service quality variable (Y) is at 61,7% category of 47 respondent of society and employees.Internal work environment and quality of public service, calculated through SPSS has a relationship of 0.740%,meaning that both variables are strong and significant from the significant (2-tailed) value of 0.00 <0.05. Thecontribution of internal work environment variable to the quality of public service is 54,7%. It means that thevariation of public service quality change is influenced by internal work environment variation and the rest is54,3% influenced by other factors.This study aims to determine whether there is influence between the internal work environment with the qualityof public services. The research hypothesis tested is the extent to which the internal work environment affectsthe quality of public services in the Department of Population and Civil Registry of Southeast MinahasaRegency. The research method used is the method of observation, interview, questionnaire and documentation.Keywords: Internal Work Environment, Quality of Public Service.